Cannibalistic Caterpillars (Utetheisa ornatrix; Lepidoptera: Arctiidae) Fail to Differentiate between Eggs on the Basis of Kinship. (1995) - Hare, James F.; Eisner, Thomas
Abstract : Utetheisa ornatrix larvae, in exercising egg cannibalism, do not discriminate between kin and nonkin. Under natural conditions this may not be a handicap, partly because the larvae hatch largely in synchrony and do not immediately upon emergence engage in cannibalism.